Lessons learned in transition: a bibliometric analysis of educational management in school transfer to provincial administrative organizations during decentralization - Chano, Jiraporn; Mohamad, Bahtiar; Prabjandee, Denchai; Singporn, Rungthip; Tuaypar, Melinda (Frontiers in Education, 2025)
This study conducts a bibliometric analysis to explore the dynamics of educational management during the transfer of schools to Provincial Administrative Organizations (PAOs) as part of Thailand’s decentralization efforts. The primary aim is to identify key themes, trends, and influential works that shape the discourse surrounding this policy shift. Using a dataset of 190 publications and authors’ keyword co-occurrence data, the study examines trends, patterns, and knowledge gaps from 2018 to 2024. By applying bibliometric techniques, including citation and co-citation analysis, the research maps the intellectual landscape of educational management within the context of decentralization. Despite a downward trend in the volume of publications, these methods remain essential for handling quantitative research data and understanding the citation patterns within the field. The findings reveal a concentrated focus on administrative challenges, stakeholder engagement, and the impact on educational outcomes. However, there is a notable lack of research addressing the long-term effects and sustainability of the management structures that have been transferred to PAOs. Additionally, the study highlights key authors, institutions, and journals that have significantly contributed to the field, showcasing an academic network of collaboration and knowledge production. This bibliometric overview provides policymakers, educators, and researchers with a consolidated view of the lessons learned during this transition. It underscores the need for continued investigation into best practices and innovative approaches to educational management in decentralized systems. Future research directions are proposed to address the identified gaps and further explore the evolving landscape of educational governance in Thailand. Ultimately, this study contributes to the broader discourse on decentralization and its implications for educational administration, offering valuable insights to inform policy and practice in similar contexts globally.